Sex and gender considerations in reporting guidelines for health research: a systematic review - Gogovor, Amédé; Zomahoun, Hervé T. V.; Ekanmian, Giraud; Adisso, Évèhouénou L.; Deom Tardif, Alèxe; Khadhraoui, Lobna; Rheault, Nathalie; Moher, David; Légaré, France (Université d'Ottawa | University of Ottawa, 2021)
Abstract Background Despite growing recognition of the importance of sex and gender considerations in health research, they are rarely integrated into research design and reporting. We sought to assess the integration of sex, as a biological attribute, and gender, as a socially constructed identity, in published reporting guidelines. Methods We conducted a systematic review of published reporting guidelines listed on the EQUATOR website ( www.equator-nework.org ) from inception until December 2018. We selected all reporting guidelines (original and extensions) listed in the EQUATOR library. We used EndNote Citation Software to build a database of the statements of each guideline identified as a "full bibliographic reference" and retrieved the full texts. Reviewers independently extracted the data on use of sex and gender terms from the checklist/abstract/main text of guidelines. Data were analyzed using descriptive statistics and narrative synthesis. Results A total of 407 reporting guidelines were included; they were published between 1995 and 2018. Of the 407 guidelines, 235 (57.7%) mentioned at least one of the sex- and gender-related words. In the checklist of the reporting guidelines (n = 363), “sex” and “gender” were mentioned in 50 (13.8%) and 40 (11%), respectively. Only one reporting guideline met our criteria (nonbinary, appropriate categorization, and non-interchangeability) for correct use of sex and gender concepts. Trends in the use of "sex" and "gender" in the checklists showed that the use of “sex” only started in 2003, while “gender” has been in use since 1996. Conclusions We assessed the integration of sex and gender in reporting guidelines based on the use of sex- and gender-related words. Our findings showed a low use and integration of sex and gender concepts and their incorrect use. Authors of reporting guidelines should reduce this gap for a better use of research knowledge. Trial registration PROSPERO no. CRD42019136491.

Highlights Omission of sex and gender considerations is a recurring deficiency in research design and reporting Integration of sex and gender considerations in health research reporting guidelines is very low Three criteria were used to assess correct use of sex and gender concepts Only one reporting guideline met the three criteria A call to action is made to address these deficiencies